Inflammation targeted nanomedicines: Patents and applications in cancer therapy. (November 2022) - Praveen, Thaggikuppe Krishnamurthy; Gangadharappa, Hosahalli Veerabhadrappa; Abu Lila, Amr Selim; Moin, Afrasim; Mehmood, Khalid; Krishna, Kamsagara Linganna; Hussain, Talib; Alafnan, Ahmed; Shakil, Shazi; Rizvi, Syed Mohd Danish
Abstract: Evident role of inflammation in cancer development and progression prompted the application of anti-inflammatory medications as a therapeutic strategy. The major bottleneck for the anti-inflammatory drugs is targeted delivery to the cancerous cell. Nanotechnology has provided safe and effective way for targeted cancer therapy. However, the complex and heterogeneous traits of cancer, incomplete information on fate and behavior of nanomedicines in human body, and lack of large-scale commercial production have slowed down the pace of nanomedicines development. To shift the paradigm from conventional cancer therapeutics to anti-inflammatory nano-therapeutics, thorough understanding of the strategies, progress, success, challenges and future perspectives are needed. The present review highlights all these aspects in addition to innovations patented on them. In fact, patent plays a vital role in protection of innovations, and further translation of lab-scale outcomes into bedside medications. Thus, the review introspects and recognizes the glitches in successful clinical translation of anti-inflammatory nanomedicines. Highlights: Inflammation plays a crucial role in the development and progression of cancer. Targeting inflammation represents a plausible strategy in cancer therapy. The review introspects and recognizes the glitches in successful clinical translation of anti-inflammatory nanomedicines. The review summarizes the patents and applications of anti-inflammatory nano-therapeutics in cancer therapy.